2020
DOI: 10.3390/en13112765
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Sensitivity of Decline Curve Modelling

Abstract: The development of prediction tools for production performance and the lifespan of shale gas reservoirs has been a focus for petroleum engineers. Several decline curve models have been developed and compared with data from shale gas production. To accurately forecast the estimated ultimate recovery for shale gas reservoirs, consistent and accurate decline curve modelling is required. In this paper, the current decline curve models are evaluated using the goodness of fit as a measure of accuracy with field data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The ARIMA model can distinguish patterns of time series well but not data patterns that are nonlinear, whereas ANN can only handle nonlinear data. Therefore, hybrid models link the benefits of ARIMA with respect to linear modeling and ANN in terms of nonlinear edge modeling, while, in certain conditions, the single-model approach can outperform hybrid models …”
Section: Model Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The ARIMA model can distinguish patterns of time series well but not data patterns that are nonlinear, whereas ANN can only handle nonlinear data. Therefore, hybrid models link the benefits of ARIMA with respect to linear modeling and ANN in terms of nonlinear edge modeling, while, in certain conditions, the single-model approach can outperform hybrid models …”
Section: Model Overviewmentioning
confidence: 99%
“…An accuracy assessment has shown that decline curve modeling influences the estimated ultimate recovery (EUR) of SGRs and the different decline curve models result in different EUR results, which is either over- or underestimated . Previous research has shown that production time considerably influences the EUR, which is dependent on the decline curve model being used .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current reservoir simulation techniques that are used in forecasting conventional oil and gas wells still face some challenges when it comes to forecasting unconventional resources due to challenges in modeling [3], costly data acquisition [4], complex fracture network [5] and variation of fracture permeability [6]. Another approach used to forecast unconventional gas resources is decline curve analysis (DCA) in which different models have been developed and used over the years [7,8]. Some of these decline curves were developed from physical interpretation of gas flow [9,10] and some of them are developed empirically based on observations [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Decline curve modeling has been used to predict production data where the curve is fitted to the data to estimate future points. In [15], different decline models are evaluated, namely the Exponential Decline Model (SEDM) and the Logistic Growth Model (LGM), followed by the Extended Exponential Decline Model (EEDM), the Power Law Exponential Model (PLE), Doung's Model, and the Arps Hyperbolic Decline Model.…”
mentioning
confidence: 99%